Regulação emocional, satisfação sexual e comportamento sexual de risco em mulheres vítimas de abuso sexual na infância - Krindges, Cris Aline (2016)
Child sexual abuse (CSA) is considered a public health problem. It includes social, cultural, psychological, medical and legal aspects, and it can be an inciting factor of different consequences for the human development. This thesis aimed to observe women who were CSA victims and the consequences for adulthood, concerning emotion regulation, sexual satisfaction and risky sexual behavior. The research consists of two articles: the literature narrative review and the empirical study. The literature narrative review focuses on the CSA through empirical studies review on this theme. Some significant CSA consequences were verified in the sexual satisfaction scope, such as the lack of pleasure, besides the sexual aversion and avoidance. However, there are some opposite results in which CSA victims also presented major excitation, sexual desire and satisfaction in sexual relations. The review study showed there is no unanimity in literature and the CSA may affect the sexual satisfaction in different ways. In the empirical study, I aimed to investigate the CSA consequences for emotion regulation, sexual satisfaction and risky sexual behavior based on a descriptive and exploratory analysis. Eight women over the age of 18 and presenting some CSA episode were subjects for this study. The evaluation occurred through self-report scale and semi-structured interview and results showed that all the evaluated CSA victims presented different levels of emotion dysregulation. In regard to sexual satisfaction, in some cases, women reported difficulties, whereas others reported the preservation of their sexual desire and satisfaction. Risky sexual behaviors were identified in only two cases and remitted the sexual experiences of the past. These results are relevant for understanding potential long-term CSA repercussions and helping with effective psychological intervention for specific cases of women with history of sexual victimization in childhood.